A word from our Editor-in-Chief: WE PROPOSE A YEAR 2022 WITH VERY GOOD RESULTS ! (Nonconventional Technologies Review, 2022)
Through these lines we will present the first issue of the review in 2022. This first issue of 2022 contains original researches written by well-known authors in the field. The scientific papers were presented at the QIEM - ICNCT 2021 Conference on the 18th and 19th of November 2021, conference held in Cluj Napoca. The conference took place online but even in these conditions the participation was numerous.